Dosage effects of extracorporeal shockwave therapy in early hip necrosis. (November 2016) - Wang, Ching-Jen; Huang, Chung-Cheng; Yip, Hon-Kan; Yang, Ya-Ju
Abstract: Background: This study investigated the effects of different dosages of extracorporeal shockwave therapy (ESWT) in early osteonecrosis of the femoral head (ONFH). Materials and methods: Thirty-three patients (42 hips) were randomly divided into three groups. Group A (10 patients with 16 hips) received 2000 impulses of ESWT at 24 Kv to the affected hip. Group B (11 patients with 14 hips) and Group C (12 patients with 12 hips) received 4000 and 6000 impulses of ESWT respectively. The evaluations included clinical assessment, radiographs, dynamic contrast-enhanced MRI for microcirculation (K trans ) and plasma volume (Vp), and blood tests for biomarker analysis (NO3, VEGF, BMP-2, osteocalcin, TNF-α, IL-6, substance P, CGRP, DKK-1 and IGF). Results: Significant differences of pain and Harris hip scores were noticed between Group A and C in 6 months after ESWT (all P < 0.05). The pain score decreased, but not Harris hip score improved over the observation time period from 6 to 24 months. Total hip arthroplasty was performed in 3 patients (4 hips) in Group A, but none in Groups B and C. Group C showed significant changes in serum biomarkers for angiogenesis, osteogenesis, anti-inflammation, pain threshold and tissue regeneration between one week and one month after treatment (all P < 0.05). However, no significant changes in the infarction volume in image studies were noted in all groups (all P > 0.05). The post-treatment K trans and Vp in the peri-necrotic areas of Group B and C were significantly greater than pre-treatment data (both P < 0.05). Conclusions: High dosage ESWT is more effective in early stage ONFH. The systemic beneficial effects of ESWT may ultimately enhance angiogenesis with improvement of microcirculation of the peri-necrotic areas, that in turn, can improve subchondral bone remodeling and prevent femoral head collapse. Highlights: High dosage of extracorporeal shockwave therapy is more effective in early osteonecrosis of the femoral head. The systemic beneficial effects may improve angiogenesis, osteogenesis, anti-inflammation, pain threshold and tissue regeneration. Ultimately, the therapy can enhance microcirculation of perinecrotic areas and prevent femoral head collapse.